Electrophoretic deposition of multi-walled carbon nanotubes on stainless steel for ethanol sensor - Chaudhary, Mangal; Chaudhary, Rima; Shrestha, Sabita (Scientific World, 2025)
Ethanol sensors are attracting tremendous interest because of their wide spread application in industry, environmental monitoring, space exploration, biomedicine and pharmaceuticals. This paper describes the feasibility study and investigation of electrophoretic deposition of oxidized MWCNTs for the application in ethanol sensor. MWCNTs are used to obtain thin film by electrophoretic deposition. The oxidized MWCNTs were characterized by FTIR. The uniform electrophoretic deposition of MWCNTs are confirmed by SEM. Raman spectroscopy confirmed the MWCNTs as deposited material. The resistance of electrophoretic deposition material was measured in closed glass chamber. Then sensitivity percentage was calculated. It was observed that the rate of % sensitivity increases with time and became saturated after certain time.